1981
DOI: 10.1111/j.1471-0528.1981.tb00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Cefuroxime: Potential Use in Pregnant Women at Term

Abstract: Summary The placental transfer of cefuroxime was studied in 20 women after one or more 1.5 g intravenous injections. Ten women had labour induced at term and ten were delivered by elective Caesarean section. High concentrations of cefuroxime were found in the cord blood and amniotic fluid and therapeutically active antibiotic levels were found in the infants for up to six hours after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 2 publications
4
16
0
Order By: Relevance
“…The highest levels of cefuroxime in plasma of pregnant patients with preterm premature rupture of the membranes, i h after intravenous injection of 1,500 mg cefuroxime, were similar to those of other investigators [13]. Also the plasma levels found 8 h after injection, and the levels in vaginal amniotic fluid were similar [13]. As expected, the amniotic fluid cefuroxime levels were higher than those reported by other investigators, who injected 750 mg cefuroxime intramuscularly or intravenously, or 1,000 mg cefuroxime intravenously [12 14-16].…”
Section: Pharmacokineticssupporting
confidence: 89%
See 3 more Smart Citations
“…The highest levels of cefuroxime in plasma of pregnant patients with preterm premature rupture of the membranes, i h after intravenous injection of 1,500 mg cefuroxime, were similar to those of other investigators [13]. Also the plasma levels found 8 h after injection, and the levels in vaginal amniotic fluid were similar [13]. As expected, the amniotic fluid cefuroxime levels were higher than those reported by other investigators, who injected 750 mg cefuroxime intramuscularly or intravenously, or 1,000 mg cefuroxime intravenously [12 14-16].…”
Section: Pharmacokineticssupporting
confidence: 89%
“…The minimum and maximum levels were 9. The highest levels of cefuroxime in plasma of pregnant patients with preterm premature rupture of the membranes, i h after intravenous injection of 1,500 mg cefuroxime, were similar to those of other investigators [13]. Also the plasma levels found 8 h after injection, and the levels in vaginal amniotic fluid were similar [13].…”
Section: Pharmacokineticssupporting
confidence: 83%
See 2 more Smart Citations
“…Bousfleld et al reported comparable data, with intravenous injections of 1,500 mg cefuroxime every 4 h until delivery [23]. After one dose, the concentration in the amniotic fluid ranged from 0 to 43.4/zg/ml, 6 and 34/zg/ml after 2 injections and 77.8 /~g/ml after 3 injections.…”
Section: Pregnancymentioning
confidence: 63%